Propensão a exportar em países emergentes: análise em uma população de granjas - Mello, Claudio Bezerra de (2023)
Exporting has been the most common way of accessing foreign markets, as it is the least expensive and least risky. Although exporting brings benefits to companies and the host country, the number of companies that export, in several countries of emerging economies such as Brazil, is low when compared to countries of developed economies. In the Brazilian egg production market, Brazil is the sixth largest producer in the world, but exports less than 1% of production (United Nations Food and Agriculture Organization - FAO). Faced with this reality, why do farmers, who have the productive and technological capacity to produce more and export, not do so? To analyze this controversial issue, it is necessary to analyze which factors interfere for this low export to happen, that is, I have to analyze the propensity to export from Brazil. The overall objective is to analyze the concept, theories and factors that impact the export propensity of companies in emerging countries to contribute both to the literature and to the managerial class. To achieve this objective, the thesis is developed in the format of scientific articles. A critical literature review, a study using the discrete choice technique and finally a study using the Dematel technique are developed. The first review article is based on an established methodology for literature review analysis where the concept and main factors that impact a company's propensity to export are raised. Data were collected in September 2020 from the Web of Science and Scopus databases. The sample is thirty-three articles. In the second article, the approach is quantitative and the method is the discrete choice to map how decision-making occurs in the act of exporting by farmers. Primary data are used, collected through an electronic questionnaire applied to a sample of members of the Associação dos Avicultores do Espírito Santo. The third article is also quantitative in approach, using the Dematel technique with data obtained from the previously mentioned questionnaire. Most authors of the literature review used Logit and Probit regressions, and calculated the propensity based on a dummy variable instead of the dependent variable, which is considered an a posteriori or ex post method to the fact of exporting. I question this method since the propensity is something a priori or ex ante to the fact of exporting and I offer the other two methods previously mentioned. With that, I offer alternative ways, not tested before calculating the propensity, as an a priori view to export, enriching the literature and allowing data triangulation. The fact of using alternative methods to measure the propensity to export is an unprecedented methodological contribution, since all authors use only one method, until the moment of this study. With different methods I found factors that are limiting and others that are decisive for the propensity to export as an investment, manager skills, egg prices in the international market and national competition. The fact of using other methods complements previous findings and allows a triangulation of methods, contributing to the enrichment of the literature.